Minor populations of paroxysmal nocturnal hemoglobinuria‐type cells in patients with chronic idiopathic neutropenia. (25th May 2016) - Damianaki, Athina; Stagakis, Elias; Mavroudi, Irene; Spanoudakis, Michael; Koutala, Helen; Papadogiannis, Fotios; Kanellou, Peggy; Pontikoglou, Charalampos; Papadaki, Helen A.
Abstract: Chronic idiopathic neutropenia (CIN) is an acquired disorder of granulopoiesis characterized by increased apoptosis of the bone marrow (BM) granulocytic progenitor cells under the influence of pro‐inflammatory mediators and oligoclonal/monoclonal T‐lymphocytes. Because patients with immune‐mediated BM failure display frequently paroxysmal nocturnal hemoglobinuria (PNH)‐type cells in the peripheral blood (PB), we investigated the possible existence of PNH‐type cells in 91 patients with CIN using flow cytometry. The patients displayed increased proportions of PNH‐type glycophorin A + /CD59 dim and glycophorin A + /CD59 − red blood cells (RBCs), FLAER − /CD24 − granulocytes, and FLAER − /CD14 − monocytes, compared to controls ( n = 55). A positive correlation was found between the proportions of PNH‐type RBCs, granulocytes, and monocytes and an inverse correlation between the number of PB neutrophils and the proportions of PNH‐type cell populations. The number of patients, displaying percentages of PNH‐type cells above the highest percentage observed in the control group, was significantly increased among patients with skewed compared to those with normal T‐cell receptor repertoire suggesting that T‐cell‐mediated immune processes underlie the emergence of PNH‐type cells in CIN. Our findings suggest that patients with CIN display PNH‐type cells in the PB at a high frequency corroborating the hypothesis that CIN belongs to the immune‐mediated BM failure syndromes.